When Belief Ascriptions Are About More Than What Is on Someone Else's Mind. Issue 8 (17th November 2017) - Hansen, Mikkel B.; Petersen, Esben N.; Poulsen, Arne; Salès-Wuillemin, Edith
Abstract : The third-person belief ascription, "Marie believes that the contract is in the cabinet, " may engender two interpretations: (1) It neutrally describes what is on Marie's mind and (2) it offers indirect evidence about reality, committing the speaker to the cabinet as the most likely location. The circumstances that lead to the evidential interpretation are at present not well documented in the case of belief verbs. In the case of belief-dependent verbs with and without embedding clause syntax, for example, "Marie says that the contract is in the archive, " and "Marie is looking for the contract in the archive, " it has been claimed that they eschew the evidential interpretation altogether. We explore the influence of the pragmatic context on the third-person, present tense and first-person, past tense use of the verbs, believe, say, and look for . In three experiments that manipulated the discourse context, 258 adults rated written vignettes. Regardless of the verb and the tense, when presented in discourse contexts without prior shared knowledge of the location of the object in question, the belief ascription was interpreted as indirect evidence. The results illuminate the border area between semantics and pragmatics, particularly regarding evidential uses of belief and belief-dependent verbs.